The Aesthetics and Mechanics of African Dance, Costumes and Rattles in Yibo Koko’s Seki Dance Drama - Ihunwo, Ovunda C. (Soegijapranata Catholic University, 2023)
With its distinctive form and content, African dance stands apart, carving out a unique identity that sets it apart from other continents. Its inherent rhythm possesses a magnetic quality capable of compelling people to move, transcending language barriers—an attribute that has propelled African musicians, particularly those from Nigeria, to a dominating position on the global music stage. This paper delves into traditional African dance, explicitly focusing on the rhythmic opulence found in the dance of rattles, costumes, and water pots within Seki. This captivating dance drama pays homage to the vibrant culture of the Niger Delta in Nigeria, Africa. Authored by Yibo Koko, the Seki dance drama undergoes a transformative journey, skilfully repackaging the traditional village square theatre into a digitalized theatrical experience accessible both as a live performance and in the dynamic space of new media. The paper employs a robust methodology and theoretical framework, drawing on dance theories, historical surveys, and analytical reviews of Seki performances to unravel the nuanced layers of this artistic expression. In scrutinizing Seki, this paper not only sheds light on the captivating exploration of rhythmic elements, including rattles, costumes, and water pots, but also underscores the broader impact of Seki's performance. The dance drama is a compelling canvas that radiates colours and a flawless rhythm, capturing global attention and playing a pivotal role in restoring the splendour of African ancestry. Through this repackaged theatre experience, Seki becomes a vehicle for exporting African culture, offering a renewed perspective that transcends borders and celebrates the rich heritage embedded in the dance's vibrant tapestry.